PROFESJONALIZM NEOFILOLOGA JAKO NAUCZYCIELA AKADEMICKIEGO WOBEC ZJAWISKA WIELODYSKURSYWNOŚCI W GLOTTODYDAKTYCE - Karpińska-Musiał, Beata; Orchowska, Izabela (Neofilolog, 2019)
The paper presents and discusses the concept of the discourse competence of an academic FL teacher as a researcher and a professional. For the sake of theoretical argument we also investigate the different kinds of discourse competence present in FL teaching and learning. We propose that discourse competence should be the object of continuous development for teachers who aspire to develop their disciplinary and epistemological awareness: two components of a teacher’s professionalism we consider indispensable in the teaching and learning process.